A Prospective Observational Study on the Therapeutic Effect of Plantago Major in Reducing Craving for Tobacco - Shukla, Indu (Homœopathic Links, 2019)
Background and Objectives Tobacco Dependence is a well acknowledged social and health evil. In India, 8–9 lakh persons die every year due to Tobacco related diseases Numerous studies show that tobacco cessation leads to considerable decrease in health risks posed by tobacco use. Therefore there is a need that homoeopathic medicines should be incorporated in the treatment of tobacco cessation, as it is very palatable and will have no such side effect. Moreover, there is not much documented research evidence about the usefulness of homoeopathic system of therapeutics in tobacco cessation. Main objective of the study is to ascertain the effects of Plantago major in modifying craving for Tobacco.Methods Prospective study was conducted in randomly selected 30 patients attending the outpatient, inpatient of Bakson Homeopathic Medical College and Hospital. Adults of age group 15–60 who showed tobacco dependence were included in the study. In this study cases were reviewed in every 2 weeks. Outcome of study were measured by fagerstrom test score changes.Result It was noted that out of 30 cases, 27(90%) cases showed change in Tobacco dependence, 3(10%) cases didn’t show any change. To assess this change in tobacco dependence fagerstrom test score of patients before and after treatment were taken into consideration. The statistical analysis was done using the paired t test. Significance was accepted at p value < 0.05 to assess differences before and after taking medicine. Baseline Mean ± SD FTND was 6.93 ± 1.41 which improved to 5.33 ± 1.32 after treatment. A paired student t test showed that the above changes were statistically significant (p < 0.005) which shows a significant reduction in patient’s tobacco dependence. p-Value is < 0.001 which is significant this shows that Plantago major has effect in reducing craving for tobacco.Conclusion These results confirm the age old observations of homoeopathic stalwarts regarding the use of Plantago Major in reducing craving for tobacco especially in the present scenario when large number of tobacco users were planning or thinking of quitting tobacco use.
Keywords: FTND score; Plantago; tobacco dependence